Traffic Effectiveness by Law Enforcement Community Through Which are Ticketed Traffic Law in Police of Pekalongan - Bobby Anugrah Rachman; Anis Mashdurohatun; Achmad Sulchan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aimed to analyze the effectiveness of enforcement by the Traffic through ticketed to the people who violate traffic in the jurisdiction of Police Pekalongan and analyze barriers to enforcement by the Traffic Police Pekalongan against people who commit traffic violations, as well as the solution.The method used is empirical juridical approach or in other words the socio-juridical. Specifications research is descriptive. In this study the analysis used is qualitative analysis.The results of this study were: 1) The enforcement of the law by speeding ticket Satlantas through to the people who violate traffic in the jurisdiction of Police Pekalongan have been effective. Law enforcement jurisdiction over a speeding ticket in Pekalongan Police can provide a deterrent effect against traffic offenders, violations be reduced and the number of traffic accidents decreased. 2) Obstacles and solutions enforcement by the Traffic Police Pekalongan against people who commit traffic violations include: Offenders traffic still does not have a deterrent effect because until now there are many traffic violations, the lack of personnel in the line of duty, inadequate number of vehicles Pekalongan is owned by traffic Police, there are still people who do not know about the traffic rules, there is still a cultural one, that there are parents that when her son gets ranking in school, then bought a motorcycle as a gift. The solutions or efforts made to overcome obstacles in enforcement by the Traffic Police Pekalongan: Enforcing the law indiscriminately through seminars and trainings, submitted a letter to the leaders for additional personnel, proposed the budget and facilities and amenities, add socialization schedule traffic rules, instilling a culture of orderly traffic among early age.Keywords: Law Enforcement; Traffic Ticketed; Traffic Violations.